Kejahatan Terselubung di Balik Kertas Suara Tidak Sah yang Gagal Dicegah oleh Pasal 46 Peraturan KPu No.16 Tahun 2010 - Simanihuruk, M. (Jurnal Konstitusi, 2010)
Article 46 KPU Regulation No.16 of 2010 count the percentage of  the gaining votes of each candidate pair from the total of valid ballot  paper. The invalid ballot paper is totally neglected. Thus the democratic right of those people who has an invalid votes is neglected as well. More over a danger implication of this article is a hidden crime that can be planned systematically by increasing the percentage of the gaining votes through out the invalid ballot paper. The more the number of invalid ballot paper,  the most the percentage of the gaining votes. If a total number of valid votes  is a for a candidate  pair A,  a total number  of valid votes  is b for a candidat pair B, according to the survey for example, and a/ (a+b) < b/(a+b) then a candidate pair A can  increase  mathematically their gaining votes to at least 30,01 % by planning at least t + s total number of invalid ballot paper such that t and s satisfy the inequality s>b – 69.99(a-t)/30.01 where t is the number of invalid ballot papers that should be subtracted from the total gaining vote of the candidate pair A and s is the number of invalid ballot papers that should be subtracted form the total gaining vote of the candidate pair B. This type of a hidden crime some time can be detected by the statistic but some time can not. The detectable hidden crime can be analyzed by Chi-Square formula. This paper provide a simulation how to detect these type of hidden crime. We use the Chi-Square formula, with 0.05 level of significance, to detect these hidden crime. The paper begin with the simulation how to increase the gaining votes at least 30,01 %.